Frequency of Modifiable Cardiovascular Risk Factors Such as Obesity, Diabetes Mellitus and Hypertension in a Benin Rural Area - ZANNOU, DJIMON MARCEL; AGBODANDE, KOUESSI ANTHELME; AZON KOUANOU, ANGÈLE; WANVOEGBE, FINANGNON ARMAND; CODJO, LEOPOLD; DOVONOU, ALBERT; BAGLO, TATIANA; HOUNGBE, FABIEN (My University, 2015)
The fight against cardiovascular diseases requires the knowledge of their modifiable risk factors. This study aimed to assess the level of modifiable cardiovascular risk factors in a rural area in order to develop a prevention program. Methods: This is an analytical and cross-sectional study on data collected during a fairground medical consultation of adults from 20 to 25 May 2013, in both border districts of the municipality of Djidja (Agouna and Houto). The studied parameters were the capillary blood glucose profile, blood pressure profile, waist circumference (WC) and Body Mass Index (BMI). Diabetes is defined by a fasting blood glucose ≥ 1.26 g/L two times. Hypertension is defined according to the criteria of JNC VII and obesity by BMI ≥ 30 kg/m2; abdominal obesity is defined by a WC above 102 cm in men and 88 cm in women. Data were analyzed using SPSS software version 18.0. Results: A total of 926 people were included among whom 57.8% were women. The average age was 38.43 ± 15.84 years. The prevalence of diabetes mellitus was 2.9%. The prevalence of obesity (BMI ≥ 30 kg/m2) was 8.4%; 10.8% of studied population had abdominal obesity and 19.2% had hypertension. Age above 35 years and obesity were significantly associated with hypertension. Risk factors of obesity (IMC ≥ 30 kg/m2) were the place of residence (Agouna), the female gender, age between 35 and 64 and abdominal obesity. Conclusion: The frequency of cardiovascular risk factors, although small compared to the national level, remains a concern in the investigated rural communities. This must lead to undertake a survey on the lifestyle and dietary
Keywords: Rural Area; Cardiovascular Risk Factors; Diabetes Mellitus; Hypertension; Obesity